The influence of workplace environment on workers’ welfare, performance and productivity (2012)
The study analyzed the influence of workplace environment on workers welfare and productivity in government parastatals of Ondo State, Nigeria. Two research questions are raised to assist the research. The study adopted the descriptive survey research design of the ex-post facto type. The random sampling technique was used to select 350 respondents. A structured questionnaire with three sub-sections was used to collect data that were analyzed with mean values and simple percentages. The results showed that workplace features and good communication network at workplace have effect on worker’s welfare, health, morale, efficiency, and productivity. It was recommended that industrial social workers should advocate with management to create a conducive workplace environment and good communication network that will attract, keep, and motivate its workforce for healthy living and improved productivity and guarantee virile employees, enthusiastic employers and sustenance of the organization.